The Semiotics of Typography in Visualising Verbal Messages of Fear in Visual Communication - Zantides, Evripides (My University, 2023)
Fear appeals are widely studied in the field of social marketing communications and have been used in various advertising contexts, for example, in anti-smoking or alcoholism treatment campaigns, as well as to promote, or oppose political ideologies in electoral campaigns. For LaTour & Zahra (1988), fear is an inherent instinct that can sometimes influence and trigger human behaviour. It produces feelings of unease and stress, which motivate people to look for ways to alleviate them. As people's fear responses are acquired through experience, marketers frequently employ such appeals to generate interest in their products or services. In fact, many studies have examined the function of fear requests and their effectiveness on people's responses based on their audio-visual structure. However, there is currently no research evidence on the semiotic impact of typography and letterforms to evoke fear through verbal messages in visual communication. The current paper aims to study the visualisation of verbal messages in various examples from visual communication, like film posters, book covers, album music covers, advertisements, logos etc. A semiotic analysis will be implemented in specific examples, using the semiotic dimensions of Typography as defined in the compiled model of Zantides (2018), and particularly explore the variables of visual hierarchy, shape, size, value, texture, colour, orientation, placement and connotative linguistic meaning. The results show that additional appeals are visually imbedded through Typography, and while verbal language has its own linguistic power, visual codes of fear through shape, texture and colour are often used to horrify connotatively the message.
Keywords: Visualisation; Verbal messages; Semiotic analysis